Whole-genome sequencing reveals a previously unrecognized measles virus cluster in Burundi - Néhémie Nzoyikorera; David F. Nieuwenhuijse; Leonard Schuele; Cassien Nduwimana; Armstrong Ndihokubwayo; Théogène Ihorimbere; Denis Niyomwungere; Hayley Cassidy; Marjan Boter; Celestin Nibogora; Richard Molenkamp; Alexis Niyomwungere; et al. (PLoS ONE, 2026)
Despite remarkable progress towards measles elimination in Burundi, the country has seen a resurge in cases since 2019. Epidemiological investigations have been performed; however, it remained unclear if all measles cases involved in recent outbreaks were linked or caused by multiple independent events including introductions from other countries. Therefore, the objective of this study is to investigate the genetic diversity and evolution of measles virus (MeV) during the last large MeV outbreak in Burundi in 2024. The study was carried out on oropharyngeal swab samples collected from four neighboring health districts. Amplicon-based MeV sequencing was performed on the MinION Mk1D. Consensus sequences were generated from 18 isolates and phylogenetic and Bayesian evolution analysis including 152 closely related public genomes were performed. Results showed that all 18 newly generated whole-genome sequences belonged to the genotype B3. Phylogenetic analysis revealed a diverse population of MeV circulating in Burundi, with sequences divided into two separate clusters. The first cluster consisted of two sequences and was most closely related to Italian sequences, while the second cluster was more related to local transmission in the Great-Lakes region based on the N450 region. Based on whole-genome sequences, the remaining 16 whole-genome sequences from Burundi clustered with one sequence from the Netherlands. The most recent common ancestor of the sequences in the second cluster was estimated to be around the beginning of 2023 (between the end of 2022 and the end of 2023 using the 95% confidence intervals) by using Bayesian evolutionary analysis. Here, we provide the first batch of MeV whole-genome sequences generated on the African continent of the ongoing MeV outbreak in the Great Lakes region of Africa. Using these whole genome sequences, we demonstrated that measles viruses genotype B3 were already circulating in Burundi since the beginning of 2023 well before the outbreak in 2024 was noted. We also showed that the recurrent measles outbreaks in Burundi are ignited from different sources, showing that measles in Burundi is sustained by multiple introductions and emphasizing the importance of ongoing molecular surveillance for elimination efforts.